Disordered eating in elite youth athletes: A scoping review of studies published since 2000 - Maxwell Marrows; Hilary Grover; Georgina Buckley; Nikki A. Jeacocke; Courtney C. Walton (JSAMS Plus, 2023)
Objectives: The purpose of this scoping review was to explore what is known about eating disorders and disordered eating in elite youth athletes aged 12–18. This review intended to explore what is known about the prevalence, risk factors, and outcomes of these conditions. Design: Scoping Review. Method: A scoping review was conducted following the Johanna Briggs Institute (JBI) and Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) methodology. Six key databases were searched to identify articles for inclusion: PsycInfo, MEDLINE, CINAHL, SPORTDiscus, Scopus, and Google Scholar. Data was subsequently extracted and summarised in line with the research questions. Results: In total, 21 studies were found that met inclusion criteria. The included studies overwhelmingly focused on girls, European populations, and used a cross-sectional quantitative study design. Where clinical interview was used, there were higher rates of eating disorders among elite youth athletes compared to the general youth population. The most cited risk factors included female gender, leanness sports, and those with higher body mass index. Eating disorders and disordered eating were found to be associated with higher rates of depression and anxiety but there was limited investigation of other associated outcomes. Conclusions: Findings from this review suggest that elite youth athletes are at risk of eating disorders and disordered eating. However, significant limitations in the field exist and further research is needed using clinical interview and population specific screening tools to better understand the prevalence, risk factors and outcomes of disordered eating and eating disorders to support this population.